2006
DOI: 10.1359/jbmr.020603
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of the Inorganic Phosphate Transporter Pit-1 Is Involved in BMP-2–Induced Matrix Mineralization in Osteoblast-Like Cells

Abstract: Pi handling by osteogenic cells is important for bone mineralization. The role of Pi transport in BMP-2-induced matrix calcification was studied. BMP-2 enhances Pit-1 Pi transporters in osteogenic cells. Experimental analysis suggest that this response is required for bone matrix calcification.Introduction: Bone morphogenetic proteins (BMPs) are produced by osteogenic cells and play an important role in bone formation. Inorganic phosphate (Pi) is a fundamental constituent of hydroxyapatite, and its transport b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
78
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(82 citation statements)
references
References 36 publications
4
78
0
Order By: Relevance
“…Many osteotropic factors regulate phosphate uptake are associated with osteogenic differentiation and mineralization in osteoblasts. Upregulation of Pit-1 may be a common mechanism by which osteotropic factors, such as BMP-2, TGF-β and PDGF, promote biomineralization [20,21,32]. Consistent with these studies, we previously reported that phosphate uptake via Pit-1 was also required for SMC calcification, suggesting a crucial role of Pit-1 in osteogenic differentiation and mineralization of SMC [8].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Many osteotropic factors regulate phosphate uptake are associated with osteogenic differentiation and mineralization in osteoblasts. Upregulation of Pit-1 may be a common mechanism by which osteotropic factors, such as BMP-2, TGF-β and PDGF, promote biomineralization [20,21,32]. Consistent with these studies, we previously reported that phosphate uptake via Pit-1 was also required for SMC calcification, suggesting a crucial role of Pit-1 in osteogenic differentiation and mineralization of SMC [8].…”
Section: Discussionsupporting
confidence: 79%
“…Csiszar et al showed that ERK and PKC play important roles in BMP-2-induced proinflammatory phenotype in endothelial cells [19]. In addition, JNK and PI3-kinase are also involved in BMP-2-upregulated Pit-1 expression [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the activation of these pathways can regulate the induction of genes such as osteopontin and type I collagen, of which products play an important role in the process of osteoblastic mineralization (Hipskind and Bilbe, 1998). Recently, the involvement of ERK and JNK activation in the induction of ALP activity and the matrix mineralization have been reported in MC3T3-E1 cells (Hanai et al, 2006;Suzuki et al, 2006). However, considering that the ERK and JNK cascades target an overlapping but not identical set of genes (Hipskind and Bilbe, 1998), Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Bone morphogenetic protein 2 (BMP-2) induces osteoblastic differentiation by acting directly on mesenchymal stem cells (MSCs), increasing expression of the osteogenic transcription factors osterix and RUNX2. 5,6 In addition, BMP-2 stimulates osteoblastlike cells to produce alkaline phosphatase (ALP) and to calcify their extracellular matrix, 7,8 and longterm exposure to BMP-2 induces apoptosis. 9 This suggests that cells must be competent to respond to differentiation signals and that the downstream effects of the signal depend on the differentiated status of the responding cell population.…”
mentioning
confidence: 99%